2019
DOI: 10.1111/sjop.12531
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional resilience in treatment‐seeking patients with obsessive‐compulsive disorder and its association with treatment outcome

Abstract: There is a lack of research on the relation between obsessive-compulsive disorder (OCD) and resilience. Dispositional resilience, as described and defined in literature on hardiness, consists of three facets, namely beliefs about having control in everyday living, having a sense of purpose or commitment, and a positive attitude toward challenges. This study explores associations between dispositional resilience (measured with the Dispositional Resilience Scale (DRS-15-R)), symptom severity, and treatment outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
3
6
0
Order By: Relevance
“…However, studies on resilience in OCD patients are limited. In this study, we found that resilience levels in the OCD patients were lower than those in the general population ( Yu et al, 2007 ), which was consistent with a previous study ( Holm et al, 2019 ). Studies have found a negative association between resilience and negative emotion, and this correlation is mainly driven by optimism ( Chen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, studies on resilience in OCD patients are limited. In this study, we found that resilience levels in the OCD patients were lower than those in the general population ( Yu et al, 2007 ), which was consistent with a previous study ( Holm et al, 2019 ). Studies have found a negative association between resilience and negative emotion, and this correlation is mainly driven by optimism ( Chen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Individuals among the public with high levels of mental resilience would have lower levels of anxiety and depression during the COVID-19 pandemic ( Song et al, 2020 ). OCD patients had lower dispositional resilience scores than control groups, and resilience was negatively associated with OCD symptoms ( Holm et al, 2019 ). Studies have found that resilience is associated with many psychosocial factors, such as active coping and performance, cognitive flexibility, a feeling of control, harm avoidance and social support ( Eley et al, 2013 ; Iacoviello and Charney, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our risk factor hypothesis was partially supported. We confirmed previous findings that emotion dysregulation, AS (under certain conditions of perceived COVID-19 impact), and low resilience are associated with OC symptom severity (Berman et al, 2018 ; Holm et al, 2019 ; Khosravani et al, 2020 ; Yap et al, 2018 ). These results map onto clinical observations that the pandemic has not affected individuals uniformly—those who lack resources to recover quickly from stressful events or those who lack awareness of emotions and are less able to mount adaptive responses to them are at highest risk of deterioration.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals at highest risk and who require closer monitoring during the COVID-19 pandemic may be those who have lower resilience and higher emotion dysregulation or AS. Although we are conceptualizing these constructs as trait factors, we do not mean to imply that such dispositional factors are not malleable; resilience in particular has been shown to improve with treatment among people with OCD (Holm et al, 2019 ). In addition, several of the adaptive self-reliant coping strategies that predicted subsequent-week reductions in OC symptoms reflect skills that are taught during effective psychological treatments for OCD and depression, such as positive reframing (cognitive therapy; Wilhelm & Steketee, 2006 ), planning/active coping (behavioral activation; Lejuez et al, 2001 ), and acceptance (mindfulness; Twohig, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation